The crystal structure of (5-(2,3-dihydro-1,4-benzodioxin-6-yl)-2-sulfanylidene-1,3,4-oxadiazol-3(2H)-yl)(3-methylphenyl)methanone, C18H14N2O4S - Jiang Zi-Hui; Chen Yue-Hu (Zeitschrift für Kristallographie - New Crystal Structures)
C18H14N2O4S, triclinic, P1̄ (no. 2), a = 8.0785(6) Å, b = 8.4022(6) Å, c = 13.7881(10) Å, α = 81.537(2)°, β = 75.581(2)°, γ = 64.198(2)°, V = 815.24(10) Å3, Z = 2, R gt(F) = 0.0437, wR ref(F 2) = 0.1159, T = 273 K.